Surface-anchored tumor microenvironment-responsive protein nanogel-platelet system for cytosolic delivery of therapeutic protein in the post-surgical cancer treatment. (December 2022) - Fan, Xiaoyuan; Wang, Kaiyuan; Lu, Qi; Lu, Yutong; Liu, Fengxiang; Li, Lu; Li, Songhao; Ye, Hao; Zhao, Jian; Cao, Liping; Zhang, Haotian; He, Zhonggui; et al.
Abstract: Nanoparticle-anchored platelet systems hold great potential to act as drug carriers in post-surgical cancer treatment due to their intrinsic ability to target the bleeding sites. However, rational design is still needed to further improve its cargo release profiles to meet the cytosolic delivery of therapeutic proteins with intracellular targets. Herein, we developed a tumor microenvironment (TME)-responsive backpack-conjugated platelet system to enhance intracellular protein delivery, thereby significantly inhibiting tumor recurrence after surgery. Specifically, protein nanogels encapsulating GALA and Granzyme B (GrB) are conjugated on the platelet surface via an acid-sensitive benzoic-imine linker through a biorthogonal reaction (GALA-GNGs-P). Taking advantage of wound-tropism of platelets, GALA-GNGs-P could actively accumulate at the surgical trauma and release nanogels in response to acidic TME for promoting deep penetration. Following cellular uptake, the pore-forming peptide GALA helps nanogels escape from lysosome. Subsequently, high glutathione (GSH) concentration in tumor cytoplasm facilitates GrB release from NGs, leading to intense cell apoptosis. GALA-GNGs-P shows remarkable tumor-targeting capability, high cellular uptake, and outstanding lysosomal escaping ability, which can significantly inhibit tumor recurrence in mice models with incomplete tumor resection. Our findings indicate that platelets bioengineered with TME-responsive protein nanogels provide an option to intracellularly deliver therapeutic proteins for the post-surgical treatment of cancer. Statement of significance: Platelet-based drug delivery systems (DDSs) have gained considerable achievements in post-surgical cancer treatment. However, there is no research exploring their potential in realizing the controllable release of cargoes in the acidic tumor microenvironment (TME). Herein, we developed a TME-responsive bioengineered platelet delivery platform (GALA-GNGs-P) for achieving controllable and effective protein intracellular delivery to overcome post-surgical tumor recurrence. Our surface-anchored nanogel-platelet system has the following advantages: (i) improving the loading efficiency of therapeutic proteins, (ii) affecting no physiological function of platelets, (iii) realizing on-demand cargo release in the acidic TME, and (iv) helping proteins escape from endosomal entrapment. Our findings further explored the prospect of cellular backpack system and realized the controllable release of cargoes in the acidic TME. Graphical abstract: Image, graphical abstract